2011
DOI: 10.1152/ajpheart.00204.2011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular proton depression of peak and late Na+ current in the canine left ventricle

Abstract: Cardiac ischemia reduces excitability in ventricular tissue. Acidosis (one component of ischemia) affects a number of ion currents. We examined the effects of extracellular acidosis (pH 6.6) on peak and late Na(+) current (I(Na)) in canine ventricular cells. Epicardial and endocardial myocytes were isolated, and patch-clamp techniques were used to record I(Na). Action potential recordings from left ventricular wedges exposed to acidic Tyrode solution showed a widening of the QRS complex, indicating slowing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…[96][97][98][99] An increased window current, and a shift of voltage dependency of activation and inactivation towards positive voltages were observed in Xenopus expression system. [97][98][99] In isolated canine ventricular myocytes, a rightward shift in voltage dependency of activation but not in SSI has been shown resulting in a reduction of I Na,late .…”
mentioning
confidence: 94%
“…[96][97][98][99] An increased window current, and a shift of voltage dependency of activation and inactivation towards positive voltages were observed in Xenopus expression system. [97][98][99] In isolated canine ventricular myocytes, a rightward shift in voltage dependency of activation but not in SSI has been shown resulting in a reduction of I Na,late .…”
mentioning
confidence: 94%
“…When INa,L is recorded under AP command, there are two major type of profiles observed. In the first case the current magnitude decays monotonically; this profile was observed in dog and predicted by some of the models [68][69][70]. In the second type, the decay of transient phase is followed by a slow current accumulation during the plateau, then it forms a peak before the terminal repolarization of AP and declines rapidly reaching zero when membrane potential returns to resting level.…”
Section: Contribution Of Plateau Sodium Current To Cardiac Electric Amentioning
confidence: 66%
“…Based on these data they predicted AP lengthening at low pH in a computer model [180]. Murphy et al reported depolarizing shift in voltage dependency of activation, but not in SSI in freshly isolated canine ventricular myocytes [68,179]. In agreement with Jones et al, they observed the prolongation of AP at low pH, but they found that INa,L was reduced at in both endocardial and epicardial cells [68].…”
Section: Cellular Metabolismmentioning
confidence: 68%
See 1 more Smart Citation
“…The resting membrane potential (CL ϭ 2 s) was slightly depolarized by extracellular acidosis (control ϭ Ϫ87.1 Ϯ 2.5 mV, acidosis ϭ Ϫ83.8 Ϯ 2.7 mV; n ϭ 5, P Ͻ 0.05, paired). The effects of extracellular acidosis on cardiac AP configuration are complex, with reports of inhibition of the rapid delayed-rectifier current I Kr (8), I Ca,L (8,41), and both peak and persistent sodium current (30). In addition, we have recently shown that the changes in rabbit ventricular repolarization induced by low pH o are largely mediated by a reduction in I Ca,L and are unlikely to involve I to (41).…”
Section: Effect Of Acidosis On Action Potential Repolarization In Epimentioning
confidence: 94%